STUDY OF ACOUSTIC WAVE BACKSCATTERING TO DETERMINATION SUSPENDED SEDIMENT CONCENTRATIO - Musrianton, Muhammad
The Acoustic Doppler Current Profiler (ADCP) is used to measure current velocity and wave profiles in rivers, estuaries, and the ocean. The scattering intensity of measurement data by ADCP is possible to improve the using of ADCP, over estimation of suspended sediment concentration in the water column. This research was done use ADCP Aquadopp type production of Nortek USA. The frequency where is 300 kHz in Moro Waters, 600 kHz in Mansuar waters, 1 MHz in Gondol Waters and 1 MHz in Jatiluhur Basin. The aim of the investigation is to find mathematic equation between intencity acoustic wave backscattering with suspended sediment concentration (SSC) in the study fields. The computing of the equation base on Gartner equation (2002). Results in: 10*log10(SSC) = 1.1056*EI - 60.904 for Mansuar Waters, Raja Ampat; 10*log10(SSC) = 0.6284*EI – 19.091 for Moro Waters, Riau; 10*log10(SSC) = 0.0056*EI + 12.232 for Gondol Waters, Bali and 10*log10(SSC) = 0.1448*EI – 1.7165 for Jatiluhur Basin, Purwakarta.